Resveratrol ameliorates osteogenic differentiation, calcification, and apoptosis of VSMCs through regulating JNK/Bax signaling - Hou, Menglin; Wang, Hui; Cheng, Junmei; Duan, Xuyan; Ren, Min; Lu, Yong (Frontiers in Pharmacology, 2025)
IntroductionVascular calcification involves pathological mineralization in the vascular wall, which is characterized by the transformation of vascular smooth muscle cells (VSMCs) from a contractile phenotype to a synthetic phenotype. VSMCs undergoing apoptosis were found in vascular calcified plaques. However, the regulatory role of resveratrol in vascular calcification via VSMC apoptosis modulation remains unclear.MethodsRat VSMCs were cultured in calcifying medium (CM) to induce calcification, and treated with resveratrol, the JNK inhibitor SP600125, or the JNK activator anisomycin. Calcium deposition was assessed via alizarin red staining and quantitative calcium content assays. Alkaline phosphatase (ALP) activity, mRNA and protein levels of osteogenic markers, and apoptosis were evaluated. Molecular docking was performed to predict resveratrol-JNK binding. In vivo, vitamin D3-induced vascular calcification in mice was treated with resveratrol, and aortic calcification was analyzed via von Kossa and alizarin red staining.ResultsIn CM-induced rat VSMC calcification, resveratrol treatment effectively attenuated the calcification of VSMCs, as evidenced by reduced calcium content, ALP activity, and osteogenic markers including Runx2, BMP2, and Osterix levels. Furthermore, resveratrol treatment significantly suppressed TUNEL-positive cell proportions and caspase-3 activity in CM-treated VSMCs. Mechanistically, resveratrol treatment blocked JNK/Bax activation by reducing the p-JNK and Bax levels in CM-treated VSMCs. The JNK inhibitor SP600125 markedly reduced calcification, downregulated osteogenic markers, and inhibited apoptosis in CM-treated VSMCs. JNK activation reversed resveratrol’s anti-calcification and anti-apoptotic effects. In vitamin D3-induced calcification models, resveratrol significantly reduced vascular calcification and osteogenic differentiation.DiscussionResveratrol exerted an inhibitory effect on VSMC calcification, osteogenic differentiation, and apoptosis through the inhibition of the JNK/Bax signaling pathway.